2012
DOI: 10.1371/journal.pone.0034289
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Calorie Restriction or Dietary Resveratrol Supplementation on Insulin Sensitivity Markers in a Primate, Microcebus murinus

Abstract: The prevalence of diabetes and hyperinsulinemia increases with age, inducing metabolic failure and limiting lifespan. Calorie restriction (CR) without malnutrition delays the aging process, but its long-term application to humans seems difficult. Resveratrol (RSV), a dietary polyphenol, appears to be a promising CR mimetic that can be easily administered in humans. In this work, we hypothesized that both CR and RSV impact insulin sensitivity in a non-human primate compared to standard-fed control (CTL) animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 55 publications
2
53
0
1
Order By: Relevance
“…This explanation is, at least in part, supported by other recent studies that demonstrated that a chronic calorie restriction (e.g. animals receiving 70% calorie of the control) significantly improved insulin sensitivity and glucose tolerance without obvious changes in the body weight of the experimental animals [21]. Nevertheless, our previous studies along with the in vitro and in vivo evidence suggested that the therapeutic effects of Ex4/Fc are through GLP-1R signaling pathway.…”
Section: Discussionsupporting
confidence: 81%
“…This explanation is, at least in part, supported by other recent studies that demonstrated that a chronic calorie restriction (e.g. animals receiving 70% calorie of the control) significantly improved insulin sensitivity and glucose tolerance without obvious changes in the body weight of the experimental animals [21]. Nevertheless, our previous studies along with the in vitro and in vivo evidence suggested that the therapeutic effects of Ex4/Fc are through GLP-1R signaling pathway.…”
Section: Discussionsupporting
confidence: 81%
“…This speculation is supported by a recent study showing that neither resveratrol nor over-expression of SIRT1 enhanced the contents of cellular ATP and mitochondrial DNA in C2C12 cultures treated with AMPK-shRNA, an observation mimicked by pharmacological blockade of SIRT1 with EX527, implying that AMPK may act upstream of SIRT1 [60]. While the mechanisms underlying the finding that a 33-month resveratrol supplementation reduces the HOMA insulin resistance index without affecting body mass remains unclear [61], activation of AMPK by resveratrol may increase the enzymatic activity of SIRT1 to deacetylate and repress the hyperglycemic effects of Foxo1 and enhance the PGC-1α-related transcription cascade leading to improved mitochondrial metabolism (Fig. 2 & 3).…”
Section: The Sirt1/foxo1 Axis: a Pathway Plausibly Regulated By Ampkmentioning
confidence: 97%
“…Resveratrol treatment ameliorates abnormal insulin secretion and morphologic changes of pancreatic b cells in mice fed a high-fat diet and improves insulin resistance in rats fed fructose and in mice on a high-calorie diet (Baur et al, 2006;Bagul et al, 2012;Zhang et al, 2012a). A recent study showed that dietary supplementation with resveratrol increases insulin sensitivity and improves glucose tolerance in a nonhuman primate, the gray mouse lemur (Microcebus murinus) (Marchal et al, 2012). Curcumin treatment was evaluated in mice fed a highfat diet and was shown to prevent insulin resistance and obesity by attenuating lipogenic gene expression in the liver and inflammatory responses in adipose tissue (Shao et al, 2012).…”
Section: Phytochemicals and Adaptive Responsesmentioning
confidence: 99%